SNOW WHITE AND THE SEVEN DWARFS DRAMA: CONVERSATIONAL IMPLICATURE - Hartana, Jasar; Daulay, Sholihatul Hamidah (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
Conversational implicature is one of the most important ideas in pragmatics. The importance of conversational implicatures as a means of conveying messages is directly well established. In conducting this research, the researchers used a qualitative descriptive method. This research is qualitative because the data are in the form of words and analyzed based on the setting or natural context. Qualitative research is a type of research in which data are studied naturally without any treatment or intervention by researchers. Related to teaching English, this research helps students to know about figure of speech – how they are expressed in the context of certain situations. Referring to implicature theory, students know that conversation is more than just a series of exchanges; it consists of exchanges ideas according to norms of conversational cooperation, which can be manipulated to create various meanings. The application of conversational implicatures in Snow White and the Seven Dwarfs is in the learning process in the classroom between teachers and students. Conversational implicatures in Snow White and the Seven Dwarfs can provide several benefits and lessons for all students in learning to speak by increasing students' motivation, interest, and understanding of the learning material.